Programmable Polarization of 2D Anisotropic Rare Earth Material for Images Transmission and Encryption. Issue 5 (23rd December 2021) - Chen, Ping; Feng, Xin; Li, Dongyan; Pi, Lejing; Li, Zexin; Xu, Xiang; Wang, Haoyun; Zhou, Xing; Zhai, Tianyou
Abstract: Light manipulation has promoted applications in all‐optical processing. 2D anisotropic rare earth (RE) materials are promising for light modulation to realize information transmission and encryption due to the unique optical behaviors of RE ions. Here, image transmission and encryption have been realized by using 2D anisotropic RE material Eu2 O3 . The polarized photoluminescence (PL) of Eu2 O3 has been innovatively applied for information transmission by switching the on/off states. The opposite two modes of polarization‐dependent PL have been applied to grayscale‐resolved image transmission and encryption with high security. This novel approach, polarization manipulation on the PL of 2D anisotropic RE materials, will shed light on the development of information processing, all‐optical switch, and all‐optical computation. Abstract : This work reports 2D anisotropic rare earth (RE) materials for information transmission via the programmable polarization‐dependent photoluminescence (PL). 2D anisotropic RE materials like Eu2 O3 flakes have been synthesized. The opposite two modes of polarization‐dependent PL have been first extended to information encryption, for example, the encryption of images.